Synthesis of zinc oxide by sol-gel method for photoelectrochemical cells - Alias, Siti Salwa; Mohamad, Ahmad Azmin (SpringerBriefs in Materials,, 2014)
This book focuses on the study of synthesized ZnO powder using Zn(CH3COO)2∙2H2O precursor, methanol (as solvent), and sodium hydroxide (NaOH) to vary the pH. The successfully synthesized ZnO powder from the sol-gel centrifugation and sol-gel storage methods were characterized and investigated by X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, Fourier-transform infrared spectroscopy, UV-visible spectroscopy, and photoluminescence test to compare the properties of the nanoparticles. The best characteristic of the ZnO powder from both methods was observed when the powders were coated on an ITO glass to fabricate a PEC. The current density-voltage performances of both PECs were investigated under luminescent and dark conditions.